Intelligent handwritten recognition using hybrid CNN architectures based-SVM classifier with dropout - Amani Ali Ahmed Ali; Suresha Mallaiah (Journal of King Saud University: Computer and Information Sciences, 2022)
Text recognition in Arabic handwritten scripts is an active research field. These recognition systems face numerous challenges, including enormous open data-bases, infinite variation in people’s handwriting, and freestyle. In this manuscript, Authors model deep learning architecture which can efficiently be utilized to recognizing Arabic handwritten scripts. This work explored a new model for both single font and multi-font type which concentrate on two common classifiers which are: Support Vector Machine (SVM) along with Convolutional Neural Network (CNN). Furthermore, authors protected the proposed model against the issue of over-fitting because of the strong performance of dropout technique. Both classification and feature extraction are done automatically. In the light of the error backpropagation method analysis, authors also have been proposed an innovative depth neural network training rule for maximum interval minimum classification error. In the meantime, max-margin minimum classification error (M3CE) and cross entropy are analyzed and hybridized to obtain better outcomes. Authors tested the proposed model on AHDB, AHCD, HACDB, and IFN/ENIT databases. The proposed model performance is compared with the accuracies of text recognition gained from state-of-the-art Arabic text recognition. The proposed model delivers favorable results.